2023 Update on European Atherosclerosis Society Consensus Statement on Homozygous Familial Hypercholesterolaemia: new treatments and clinical guidance - Cuchel, Marina; Raal, Frederick J; Hegele, Robert A; Al-Rasadi, Khalid; Arca, Marcello; Averna, Maurizio; Bruckert, Eric; Freiberger, Tomas; Gaudet, Daniel; Harada-Shiba, Mariko; Hudgins, Lisa C; Kayikcioglu, Meral; et al. (European heart journal, 2023)
This 2023 statement updates clinical guidance for homozygous familial hypercholesterolaemia (HoFH), explains the genetic complexity, and provides pragmatic recommendations to address inequities in HoFH care worldwide. Key strengths include updated criteria for the clinical diagnosis of HoFH and the recommendation to prioritize phenotypic features over genotype. Thus, a low-density lipoprotein cholesterol (LDL-C) >10 mmol/L (>400 mg/dL) is suggestive of HoFH and warrants further evaluation. The statement also provides state-of-the art discussion and guidance to clinicians for interpreting the results of genetic testing and for family planning and pregnancy. Therapeutic decisions are based on the LDL-C level. Combination LDL-C-lowering therapy-both pharmacologic intervention and lipoprotein apheresis (LA)-is foundational. Addition of novel, efficacious therapies (i.e. inhibitors of proprotein convertase subtilisin/kexin type 9, followed by evinacumab and/or lomitapide) offers potential to attain LDL-C goal or reduce the need for LA. To improve HoFH care around the world, the statement recommends the creation of national screening programmes, education to improve awareness, and management guidelines that account for the local realities of care, including access to specialist centres, treatments, and cost. This updated statement provides guidance that is crucial to early diagnosis, better care, and improved cardiovascular health for patients with HoFH worldwide.
Keywords: homozygot; Cholesterol, LDL; LDL-cholesterol; hyperlipoproteinemie typ II; Anticholesteremic Agents; anticholesteremika; ateroskleróza; Humans; Atherosclerosis; Homozygote; homozygotní familiární hypercholesterolemie; Hyperlipoproteinemia Type II; Homozygous Familial Hypercholesterolemia; lidé